Adverse events related to oral hormonal contraceptive use in undergraduate pharmacy students: a cross-sectional study - Helena Constância de Melo Tozetto; Gustavo Magno Baldin Tiguman; Maria Aparecida Nicoletti; Patricia Melo Aguiar (Universidade de São Paulo, 2023)
Abstract We aimed to measure the prevalence of adverse events related to oral hormonal contraceptive (OHC) use and their associated factors in undergraduate pharmacy students. A cross-sectional study was conducted by using an online questionnaire for female students of the Faculty of Pharmaceutical Sciences of the University of São Paulo from July to August 2020. A descriptive analysis of the data was carried out, which was followed by determining the prevalence ratios to identify possible factors associated with adverse events resulting from OHC. A total of 269 valid responses were obtained, among which 50.2% (n = 135) of the students reported using OHC as a contraceptive method and 21.2% (n = 57) affirmed that they had at least one adverse event related to OHC use, which corresponds to 42.2% of those who had used OHC. The most common adverse event was headache (70.2%), and a period of less than one month was the most cited (49.1%). Only migraine comorbidity was associated with the occurrence of adverse events related to OHC. These findings reinforce the high incidence of adverse events among OHC users and the low rate of discontinuation due to these events. There is a need to provide more information on contraceptive methods to users, including its risks and contraindications.